Rare and threatened vascular plants of the railways in Slovakia - Májeková, Jana; Letz, Dominik Roman; Slezák, Michal; Zaliberová, Marica; Hrivnák, Richard (Biodiversity: Research and Conservation, 2015)
The paper presents data on the occurrence and secondary spreading of rare and threatened vascular plant species in railway habitats of Slovakia. We recorded 17 threatened vascular plant species and other 9 species that we considered to be rare in Slovakia. They grew at railway stations, mainly directly in the rail yard and also at the platforms or other similar facilities. Records of further 39 species were excerpted from literature sources. More native thermophilous species were represented among the recorded species as railway substrates provide suitable conditions for their growth. Also some archaeophytic segetal species were found quite frequent in the studied biotopes due to spreading of their seeds together with cereals transported by trains. Various habitats of railway transport facilities often provide suitable conditions for the secondary occurrence and further spreading not only of synanthropic or adventive, but also of rare and threatened plant species.